2014
DOI: 10.1002/jhbp.170
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for technical failure of endoscopic double self‐expandable metallic stent placement by partial stent‐in‐stent method

Abstract: Metastatic disease was a significant risk factor for technical failure of double SEMS placement for unresectable MHBO. The laser-cut type SEMS with a large mesh and thin delivery system might be preferable for the PSIS procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Self‐expandable metallic stents are superior to PS when carrying out biliary drainage to treat unresectable MHBO . However, opinions are yet to be established regarding drainage area, placement method, and optimal stent type . With regard to the drainage area, Mukai et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐expandable metallic stents are superior to PS when carrying out biliary drainage to treat unresectable MHBO . However, opinions are yet to be established regarding drainage area, placement method, and optimal stent type . With regard to the drainage area, Mukai et al .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, opinions are yet to be established regarding drainage area, 1,14 placement method, 15,16 and optimal stent type. [17][18][19] With regard to the drainage area, Mukai et al 1 revealed that there was no significant difference between unilateral and bilateral placement in relation to the duration of stent patency, but approximately half of the patients required bilateral drainage. Unilateral drainage may not provide adequate drainage, and bilateral drainage might be more effective physiologically for stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have examined the relationship between failure to place an endoscopic stent-in-stent SEMS and the characteristics of the patients. In one report, metastatic disease was found to be related to the failure to place an endoscopic stent-in-stent SEMS[ 17 ]. Although a similar number of patients who were evaluated in the previous investigation were analysed in this study, different results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that delayed insertion of the second SEMS by several days following the expansion of the first SEMS may also enhance the success rate of SIS deployment. Recently, Kawakubo et al described the risk factors for technical failure of SIS deployment. The rate of technical success after double guide‐wire insertion was greater when using a laser‐cut‐type SEMS with a large mesh and thin delivery system compared to the braided‐type SEMS with a small mesh and thick delivery system.…”
Section: Discussionmentioning
confidence: 99%